Telemedicine in Oculoplastics: The Real-Life Application of Video Consultation Clinics. (May 2021) - Jamison, Aaron; Diaper, Charles; Drummond, Suzannah; Tejwani, Deepak; Gregory, Maria Elena; Cauchi, Paul; Crofts, Kevin; Chadha, Vikas
Abstract : Purpose: Our oculoplastic service piloted a new video consultation (VC) clinic in response to the COVID-19 pandemic. Data were collected to determine whether specific patients are better suited to VC, and to quantify the true benefit of VC in patients that successfully attended. Methods: Data were collected prospectively on predetermined data collection forms, including consultation duration, diagnosis, management plan, and issues that arose. Results: 37.8% of new referrals and 60.9% of return patients were vetted as suitable for VC. Of those invited to attend, 83.4% agreed to a VC appointment. Of the patients appointed to a VC clinic, 71.7% (new)/75% (return) successfully completed VC, 14.9%/15.8% attempted a VC which ultimately failed, and 13.4%/9.2% did not attend. VC successfully prevented face-to-face consultation in 81.3% of new cases and 91.1% of returns. Ectropion, entropion and dermatochalasis (new referrals), and postoperative follow-up (return patients) were well suited to VC, while patients with "watery eye" (new), and lid or conjunctival lesions (return), often required face-to-face consultation. Problems (most common issues with patients connecting to the consultation, video quality, and audio quality) were encountered during 50.3% of calls, although 82.6% of attempted calls were ultimately successful. Age was not associated with the proportion of calls that were successful. Conclusions: VC is a useful tool for oculoplastic patients, irrespective of age, as long as the patient's notes/referrals are carefully vetted to determine suitability. Patients with ectropion, entropion and dermatochalasis, and postoperative reviews are better suited to VC than those with "watery eye, " lid lesions, and conjunctival lesions. Abstract : Telemedicine is a useful tool for oculoplastic patients, irrespective of age, provided that the patient's suitability is predetermined. Ectropion, entropion, dermatochalasis, and postoperative reviews seem to be well suited to video consultation clinics.